2021
DOI: 10.32674/jis.v11i4.2702
|View full text |Cite
|
Sign up to set email alerts
|

“Everything is so different...”

Abstract: In the scope of higher education internationalisation, Portuguese universities have been receiving an increasing number of students from Portuguese-Speaking countries, namely African countries, at the level of PhD studies. As highlighted in research, pursuing a PhD in an overseas context entails critical challenges for students, supervisors and higher education institutions. Against this background, this paper reports on the challenges faced by international African students attending a PhD programme in Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As stated in the methodology section, for many of these IDS, Portuguese is their second language and they speak different varieties of Portuguese. This poses them several challenges as to oral and written interaction with supervisors, to thesis writing and as to construction of data collection instruments and field work (Hu et al, 2016; Pinto, 2021). Findings show that significant differences regarding orthography, lexicon, phonology, prosody and sociolinguistic features are put forward by IDS as intervening in academic learning and in the supervisory relationship, reporting to episodes of linguistic insecurity and misunderstandings between supervisors and IDS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As stated in the methodology section, for many of these IDS, Portuguese is their second language and they speak different varieties of Portuguese. This poses them several challenges as to oral and written interaction with supervisors, to thesis writing and as to construction of data collection instruments and field work (Hu et al, 2016; Pinto, 2021). Findings show that significant differences regarding orthography, lexicon, phonology, prosody and sociolinguistic features are put forward by IDS as intervening in academic learning and in the supervisory relationship, reporting to episodes of linguistic insecurity and misunderstandings between supervisors and IDS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IDS face diverse challenges related to integration into a different pedagogical/academic culture, adaption to a different research culture, language, loneliness and homesickness (Pinto, 2021) which underline the need for intrapersonal and interpersonal qualities related to intercultural doctoral supervision. Hence, IDS in this study showed to have a clearly honed sense of the qualities they want in a supervisor, relating them to their condition of 'foreign students'.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations